A Structurally Specialized Uniform Wall Layer is Essential for Constructing Wall Ingrowth Papillae in Transfer Cells - Xia, Xue; Zhang, Hui-Ming; Offler, Christina E.; Patrick, John W. (Frontiers in Plant Science, 2017)
Transfer cells are characterized by wall labyrinths with either a flange or reticulate architecture. A literature survey established that reticulate wall ingrowth papillae ubiquitously arise from a modified component of their wall labyrinth, termed the uniform wall layer; a structure absent from flange transfer cells. This finding sparked an investigation of the deposition characteristics and role of the uniform wall layer using a Vicia faba cotyledon culture system. On transfer of cotyledons to culture, their adaxial epidermal cells spontaneously trans-differentiate to a reticulate architecture comparable to their abaxial epidermal transfer cell counterparts formed in planta. Uniform wall layer construction commenced once adaxial epidermal cell expansion had ceased to overlay the original outer periclinal wall on its inner surface. In contrast to the dense ring-like lattice of cellulose microfibrils in the original primary wall, the uniform wall layer was characterized by a sparsely dispersed array of linear cellulose microfibrils. A re-modelled cortical microtubule array exerted no influence on uniform wall layer formation or on its cellulose microfibril organization. Surprisingly, formation of the uniform wall layer was not dependent upon depositing a cellulose scaffold. In contrast, uniform wall cellulose microfibrils were essential precursors for constructing wall ingrowth papillae. On converging to form wall ingrowth papillae, the cellulose microfibril diameters increased three-fold. This event correlated with up-regulated differential, and transfer-cell specific, expression of VfCesA3B while transcript levels of other cellulose biosynthetic-related genes linked with primary wall construction were substantially down regulated.